Home-based walking program increases leg muscle strength in hemodialysis patients - Orawan Ponngeon (2018)
[Purpose] To determine the effects of a home-based walking program on lower extremity muscle strength of hemodialysis patients. [Methods] Twenty-six hemodialysis patients were divided into a training and a control group. Lower extremity muscle strength was measured using a back and leg dynamometer prior to and at the 4th, 8th, and 12th weeks of the study period in both groups. The training group performed the home-based walking program, an individually prescribed walking program which progressively increased in duration by incrementing the number of steps by 10% every two weeks. Subjects in the control group were asked to keep to their routine activities, as much as possible, during the study period. [Results] Lower extremity muscle strength in the training group remarkably increased from 52 kg at baseline to 68 kg at the 12th week (4th week = 58 kg, 8th week = 63 kg), whereas no change in the control group was found (baseline = 51 kg, 4th week = 52 kg, 8th week = 51 kg, 12th week = 48 kg). [Conclusion] A homebased walking exercise program improved lower extremity muscle strength of hemodialysis patients. Patients who have stable medical conditions should be encouraged to participate in this home-based walking exercise program to improve their abilities to perform activities of daily living.